1998
DOI: 10.1542/peds.101.5.856
|View full text |Cite
|
Sign up to set email alerts
|

Health and Developmental Outcomes at 18 Months in Very Preterm Infants With Bronchopulmonary Dysplasia

Abstract: Children with BPD-1 are similar in all respect at 18 months to children in the comparison group. Children with BPD-2 are similar to the other groups at 18 months in growth, general health, and neurologic outcome but differ in having a higher number of days of rehospitalizations for respiratory causes, more hernia repairs, and more developmental delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 30 publications
2
77
0
7
Order By: Relevance
“…25 The significant decrease in inguinal hernia repairs was surprising, but may be related to the decreased incidence of BPD with a decrease in abdominal pressure. 36 To gain an overall sense of how all babies fared with the EMPC, a cumulative mortality and morbidity index was created. This is a crude estimate, as it is not weighted for the severity of the morbidity/mortality.…”
Section: Discussionmentioning
confidence: 99%
“…25 The significant decrease in inguinal hernia repairs was surprising, but may be related to the decreased incidence of BPD with a decrease in abdominal pressure. 36 To gain an overall sense of how all babies fared with the EMPC, a cumulative mortality and morbidity index was created. This is a crude estimate, as it is not weighted for the severity of the morbidity/mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Those children with history of BPD can develop chronic reduced lung compliance and increased airway resistance (Bancalari et al, 2003). Several studies have shown that children with history of BPD often suffer from undernutrition and growth retardation (Kurzner et al, 1988;De Meer et al, 1997;Farrell and Fiascone, 1997;Gregoire et al, 1998). Evaluation of REE is a key factor in the management of children with BPD, to ensure adequate catch-up growth through intake of adequate energy.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) is a frequent complication of very premature infants, and was first described by Northway et al (Gregoire et al, 1998). Several studies have demonstrated a higher resting energy expenditure (REE) in BPD compared to healthy children of the same age.…”
Section: Introductionmentioning
confidence: 99%
“…No seguimento de crianças com idade gestacional entre 24 e 28 semanas 24 , houve diferença em relação à taxa de hospitalização por doença respiratória e ao número de dias de internação nos primeiros 18 meses de idade corrigida entre os dois grupos de crianças que utilizaram oxigênio prolongadamente (uso de oxigênio além de 28 dias de vida/uso de oxigênio às 36 semanas de idade corrigida) e as crianças do grupo de comparação. Internação ocorreu em 48% das crianças da coorte.…”
Section: Discussionunclassified
“…Internação ocorreu em 48% das crianças da coorte. As crianças que fizeram uso de oxigenoterapia às 36 semanas ficaram internadas por um período de tempo maior do que as crianças do grupo que usou oxigênio no 28º dia de vida e que as do grupo de comparação 24 . Entre as crianças do nosso estudo, a internação foi verificada em 20,5% das crianças sem uso prolongado de oxigênio e em 41,7% das que usaram oxigenoterapia por tempo prolongado (p = 0,04).…”
Section: Discussionunclassified